Burlesque West: Showgirls, Sex and Sin in Postwar Vancouver - Hunt, Gerald (Labour / Le Travail, 2011)
The article reviews the book, "Burlesque West: Showgirls, Sex and Sin in Postwar Vancouver," by Becki Ross.
Keywords: BOOKS – Reviews; BURLESQUE West: Showgirls; Sex & Sin in Postwar Vancouver (Book); Nonfiction; PROSTITUTION – History; ROSS; Becki